Fluid balance of female para hockey players during simulated competition - Gavel, Erica H.; Rae, Samantha; Logan-Sprenger, Heather M. (Frontiers in Sports and Active Living, 2024)
Purpose The purpose of this study was to characterize the hydration habits and fluid balance of female para-ice hockey players. Methods Fifteen players [5 defense (D), 8 forwards (F), and 2 goalies (G)] volunteered to participate in the study (age: 26.3 ± 10.9 y; ht:155 ± 11 cm; arm length: 65 ± 8 cm; leg length: 88 ± 11 cm; trunk length: 66 ± 14 cm). Players were weighed pre- and postgame, while fluid intake and individual playing time (PT) was monitored throughout the game. Results On average, athletes arrived hydrated to the game (USG 1.019 ± 0.006) with 40% of players arriving dehydrated (USG >1.020). Mean playing time for forwards was 11:47–28:49 min:s (18:52 ± 5:48 min:s) and for defence 13:10–18:24 min:s (15:10 ± 2.05 min:s). Sweat loss was 0.96 ± 0.64 L (0.10–2.50 L) which exceeded net fluid intake (0.61 ± 0.37 L). Mean BM loss was 0.44 ± 0.9% (−2.1 to +0.9%) with 4 of 15 players (2 D, 1 F, 1 G) losing between 1.4 and 2.1% BM. Players preferred to drink water during the game compared to a carbohydrate electrolyte solution. Conclusion 60% of athletes arrived hydrated to the game and drank enough fluid to prevent a BM loss <1%. Of note is that 40% of players arrived at the arena mildly dehydrated based on USG, and despite abundant opportunities to drink fluid during the game, 25% of players lost >1.3% BM due to sweat loss which may compromise physical and cognitive performance.